Prevalence of a zoonotic parasite, Dioctophyma renale (Goeze, 1782), among male canines in a wild riverside area of La Plata River, Province of Buenos Aires, Republic of Argentina - Burgos, Lola (2014)
Dioctophymosis is an helminthiasis with an indirect life cycle caused by Dioctophyma renale. It may affect both humans and other mammals. The purpose of this study was to determine the prevalence of the parasite in male canines of different ages, living in a wild riverside area of La Plata River with favourable characteristics for the development of eggs, intermediate or paratenic hosts and completionof the life cycle of D. renale. 171 animals were surveyed and samples were collected through urethral catheterization. The samples were processed by means of centrifugation at a relative centrifugal force of 700 g and microscopic observation of sediments. 42.1% of canines exhibited patent Dioctophymosis in their kidneys. Male canines between the ages of 2 and 5 showed the highest frequency of positive results. Several epidemiological risk factors are discussed that, when associated, might favour the high prevalence of this parasite in the area. The need for equipment for the indirect diagnosis of the disease in canines and other animals prone to infection is clearly demonstrated.